EPIPHYTIC DINOFLAGELLATES ANALYZE ON Thalassia hemprichii AT NIRWANA BEACH TELUK KABUNG DISTRICT PADANG CITY WEST SUMATERA PROVINCE - Bayu Oktavian; Thamrin '; Yusni Ikhwan Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Dinoflagellates is group of phytoplankton as a primary producer. Dinoflagellates can be planctonic also epiphytic. This research was conducted in January 2017 in Nirwana Beach Padang City West Sumatera Province which aims to determine the abundance of dinoflagellates, genera of dinoflagellates and its association with waters quality parameter used survey method. Nirwana Beach is dominated by Thalassia hemprichii, seaweed and coral reef. Purposive sampling method to select the research stations which 3 stations that represent the sampling location. Chemical and phisic waters quality measured by insitu and exsitu. The results showed that 4 genera of epiphytic dinoflagellates identified that are Amphidinium, Gambierdiscus, Ostreopsis dan Prorocentrum. The abundance of dinoflagellates is higher at 1st station with 333,18 cells g-1 and smaller at 2nd station with 224,06 cells g-1. Analysis of linear regression showed that nitrate concentration directly proportional with dinoflagellates abundance with equation y = 200,96 + 1336,7x and phospate concentration inversely proportional with dinoflagellates abundance with equation y = 345,09 + (-1868,4)x.Keywords: Dinoflagellates, Thalassia hemprichii, Nirwana Beach, Abundance